Does acute radio-frequency electromagnetic field exposure affect visual event-related potentials in healthy adults?. Issue 5 (May 2018) - Dalecki, Anna; Loughran, Sarah P.; Verrender, Adam; Burdon, Catriona A.; Taylor, Nigel A.S.; Croft, Rodney J.
Highlights: Thermal inputs to the skin were clamped for the first time to assess the impact of radio-frequency electromagnetic fields (RF-EMF) on event-related potentials (ERPs). No effects of exposure were seen on P2, N2 or P3 ERP amplitudes or latencies. Lack of ERP effects corresponds with the lack of strong evidence for RF-EMF effects on cognition. Abstract: Objective: To use improved methods to address the question of whether acute exposure to radio-frequency (RF) electromagnetic fields (RF-EMF) affects early (80–200 ms) sensory and later (180–600 ms) cognitive processes as indexed by event-related potentials (ERPs). Methods: Thirty-six healthy subjects completed a visual discrimination task during concurrent exposure to a Global System for Mobile Communications (GSM)-like, 920 MHz signal with peak-spatial specific absorption rate for 10 g of tissue of 0 W/kg of body mass (Sham), 1 W/kg (Low RF) and 2 W/kg (High RF). A fully randomised, counterbalanced, double-blind design was used. Results: P1 amplitude was reduced ( p = .02) and anterior N1 latency was increased ( p = .04) during Exposure compared to Sham. There were no effects on any other ERP latencies or amplitudes. Conclusions: RF-EMF exposure may affect early perceptual (P1) and preparatory motor (anterior N1) processes. However, only two ERP indices, out of 56 comparisons, were observed to differ between RF-EMF exposure and Sham, suggesting that these observations may be due to chance. Significance: These observations are consistent with previous findings that RF-EMF exposure has no reliable impact on cognition (e.g., accuracy and response speed).